2017
DOI: 10.1002/mnfr.201601017
|View full text |Cite
|
Sign up to set email alerts
|

Milk protein synthesis is regulated by T1R1/T1R3, a G protein-coupled taste receptor, through the mTOR pathway in the mouse mammary gland

Abstract: T1R1/T1R3 modulates the mTOR pathway to regulate milk protein synthesis in the mouse mammary gland in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 39 publications
(66 reference statements)
4
14
0
Order By: Relevance
“…The effect of lactation in the yak mammary gland by upregulating several AAT and their potential control of mTOR signaling through the import of AA into cells underscores an essential role of AAT in yak mammary gland physiology. The expression of several AAT discussed above appears to be regulated by mTOR, suggesting the crucial importance of this pathway in milk protein synthesis, which has been demonstrated previously (Liu et al, 2017).…”
Section: Short Communication: Characterization Of Gene Expression Prosupporting
confidence: 64%
See 1 more Smart Citation
“…The effect of lactation in the yak mammary gland by upregulating several AAT and their potential control of mTOR signaling through the import of AA into cells underscores an essential role of AAT in yak mammary gland physiology. The expression of several AAT discussed above appears to be regulated by mTOR, suggesting the crucial importance of this pathway in milk protein synthesis, which has been demonstrated previously (Liu et al, 2017).…”
Section: Short Communication: Characterization Of Gene Expression Prosupporting
confidence: 64%
“…These 2 AAT have a regulatory relationship with mTOR, and consequently control protein synthesis, cellular growth, and survival signaling, which might be related to cancer (Fuchs and Bode, 2005). It is reported that milk protein synthesis is regulated by T1R1/T1R3, a G protein-coupled taste receptor, through the mTOR pathway in the mouse mammary gland (Liu et al, 2017). The mTOR controls ribosome biogenesis and cell growth through several regulatory pathways.…”
Section: Short Communication: Characterization Of Gene Expression Promentioning
confidence: 99%
“…The AA sensory function of the mTOR pathway was first demonstrated in a study of hepatocyte autophagy by Blommaart et al [8], who showed that addition of AA inhibited valine release as a result of autophagic protein degradation and the effect was inhibited by rapamycin. Recently, the mTOR pathway has been shown to be critical for AA sensing and utilization in the lactating bovine or mouse MG [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…For decades, the weigh-suckle-weigh These experiments were repeated at least three times. Data are represented as means ± SD, * indicates the difference between mifepristone group and control group, * P < 0.05, * * P < 0.01, * * * P < 0.001. method has been more acceptable for its simple and effective evaluation of milk volume in mice (Boston et al, 2001;Liu et al, 2017). This method is also widely used in ruminants such as in goats or cattle (Mummed, 2012;Hogberg et al, 2016).…”
Section: Discussionmentioning
confidence: 99%